Development of polyherbal antidiabetic formulation encapsulated in the phospholipids vesicle system - Vinod Kumar Gauttam; Ajudhia Nath Kalia (Wolters Kluwer Medknow Publications, 2013)
Multifactorial metabolic diseases, for instance diabetes develop several complications like hyperlipidemia, hepatic toxicity, immunodeficiency etc., Hence, instead of mono-drug therapy the management of the disease requires the combination of herbs. Marketed herbal drugs comprise of irrational combinations, which makes their quality control more difficult. Phytoconstituents, despite having excellent bioactivity in vitro demonstrate less or no in vivo actions due to their poor lipid solubility, resulting in high therapeutic dose regimen; phospholipids encapsulation can overcome this problem. Hence, present study was designed to develop a phospholipids encapsulated polyherbal anti-diabetic formulation. In the present study, polyherbal formulation comprises of lyophilized hydro-alcoholic (50% v/v) extracts of Momordica charantia, Trigonella foenum-graecum and Withania somnifera 2:2:1, respectively, named HA, optimized based on oral glucose tolerance test model in normal Wistar rats. The optimized formulation (HA) entrapped in the phosphatidylcholine and cholesterol (8:2) vesicle system is named HA lipids (HAL). The vesicles were characterized for shape, morphology, entrapment efficiency, polar-dispersity index and release profile in the gastric pH. The antidiabetic potential of HA, marketed polyherbal formulation (D-fit) and HAL was compared in streptozotocin-induced diabetic rat model of 21 days study. The parameters evaluated were behavioral changes, body weight, serum glucose level, lipid profile and oxidative stress. The antidiabetic potential of HA (1000 mg/kg) was at par with the D-fit (1000 mg/kg). However, the potential was enhanced by phospholipids encapsulation; as HAL (500 mg/kg) has shown more significant (P < 0.05) potential in comparison to HA (1000 mg/kg) and at par with metformin (500 mg/kg).